Imidazolyl Alanes – Synthesis, Structures, and Reactivity Studies. Issue 19 (29th April 2020) - Simon, Martin; Radius, Michael; Wagner, Hanna E.; Breher, Frank
Abstract : Targeting the synthesis of Al/C based ambiphilic molecules, we investigated the dehydrohalogenation of a series of (benz)imidazole alane adducts. Depending on the steric bulk of the heterocycle, different dimeric products with various ring sizes were obtained. Dehydrohalogenation of the adduct of 1‐mesityl imidazole ( Mes Im) and 0.5 [ t Bu2 AlBr]2 furnished the dimer 2, featuring a "classical" N‐heterocyclic carbene (NHC) and a mesoionic or "abnormal" NHC (aNHC) subunit within a single molecule. The dimer is bound loosely enough to allow thermally induced isomerization of 2 into the isomers 2 NHC (all NHC) and 2 aNHC (all aNHC). Dehydrohalogenation of the adduct of 1‐mesityl‐2‐methyl imidazole ( Mes Im Me ) and 0.5 [ t Bu2 AlBr]2 (4 ) yielded the dimeric compound 5 consisting of two N‐heterocyclic olefin (NHO) subunits. Although these six‐ and eight‐membered heterocycles show no FLP‐type reactivity towards small molecules like H2, CO or CO2, we observed an ambiphilic behavior of the imidazolyl alanes during our studies. Salt metathesis reactions using Mes Im resulted in the formation of 3, which can be viewed as t Bu2 AlBr adduct of an Al/N ambiphile. Utilizing heterocycles such as benzimidazole or spiroindole provided the entry point to C–H (7, 9 ) and N–H (10 ) activation products, most likely resulting from a reactivity of intermediate species as Al/C ambiphiles. Abstract : Al/N‐based FLPs? A series of alane‐substituted imidazolyl compounds, featuring different architecture is presented. For dimeric species steric dependent formation of symmetric and an asymmetric species were observed. Reactivity studies with small molecules revealed no reactivity as hidden FLP. Nevertheless, ambiphilic behavior of the imidazolyl alanes has been observed in cases during this study.